2013
DOI: 10.5606/ehc.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a pregnant patient with bilateral traumatic bimalleolar ankle fracture: a case report

Abstract: Ayak bileği kırıkları, iskelet travmaları sonrası oluşan tüm kırıklar içerisinde giderek artan sıklıkta görülmektedir. Tüm ayak bileği kırıklarının yaklaşık %25'ini bimalleoler kırıklar oluşturmaktadır. İki taraflı travmatik bimalleoller ayak bileği kırığı ise çok nadir görülen bir durumdur. Bu tablo içerisinde aynı zamanda sezaryen doğum ile müdahale edilmiş gebelik durumunun olması, olguyu özellikle venöz tromboembolizm ve ölümcül pulmoner emboli yönünden daha da komplike hale getirmektedir. Bu yazıda, sekiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…16 There were only 6 separate cases reported in literature that are similar to our cases in being bilateral rotational type ankle injuries with some of them being identical. [10][11][12][13][14][15] Majority of the cases along with ours, were in fact as result of relatively high mechanism trauma and were associated with rotational injury patterns. This is unexpected especially when the energy absorbed caused symmetrical rotational injuries in contrast to axial type ankle fractures that commonly present as a result of high mechanism trauma.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…16 There were only 6 separate cases reported in literature that are similar to our cases in being bilateral rotational type ankle injuries with some of them being identical. [10][11][12][13][14][15] Majority of the cases along with ours, were in fact as result of relatively high mechanism trauma and were associated with rotational injury patterns. This is unexpected especially when the energy absorbed caused symmetrical rotational injuries in contrast to axial type ankle fractures that commonly present as a result of high mechanism trauma.…”
Section: Discussionmentioning
confidence: 50%
“…4,17 There were only 2 cases reported in literature that were associated with bilateral adduction or abduction moment. 10,15 Sultan et al reported a uniquely presented bilateral symmetrical supination adduction fracture dislocation as a result of a tree log falling over the patients legs while working. 15 They highlighted an important aspect in this case that is feet position at time of injury being an important aspect leading to this presentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations